Building Family Resilience Through Marital Counseling: A Literature Review - Rahma Fithri; Amirah Diniaty (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Family resilience refers to the capacity of the family system to endure, adapt, and flourish in the face of stress and adversity. Marriage counseling serves as a professional intervention aimed at helping couples resolve conflict, strengthen communication, and build a solid relational foundation. This literature review aims to analyze the role of marriage counseling in building family resilience based on national and international scientific research. The method used is a literature study by reviewing relevant academic sources. The findings indicate that marriage counseling encompassing premarital counseling, post-marital counseling, value-based counseling, and therapeutic approaches such as Emotionally Focused Therapy (EFT) and Structural Family Therapy significantly contributes to improving relationship quality, family resilience, and the psychological well-being of family members. Key success factors include active counselor involvement, couple readiness, culturally grounded approaches, and the integration of spiritual and local values. The discussion also highlights practical challenges faced by counselors, including managing uncooperative clients, emotion regulation, and value conflicts between couples. This study concludes that marriage counseling is an effective strategic instrument in realizing resilient and thriving families.